Association of Serum Hepatocyte Growth Factor Level with Systemic Inflammatory Biomarkers in Patients with Pancreatobiliary Cancer - Ünek, İlkay Tuğba and Öztop, İlhan and Başbınar, Yasemin and Ünek, Tarkan and Leblebici, Asım and Çakıroğlu, Ece and Uysal, Tuğba and Akagündüz, Baran and Ellidokuz, Hülya and Astarcıoğlu, İbrahim (Turkish Journal of Gastroenterology, 2023)
Background: Hepatocyte growth factor is a cytokine secreted by the stromal cells in the tumor microenvironment. There is little information about the clinical significance of serum hepatocyte growth factor level in patients diagnosed with pancreatobiliary cancer. The objective of the current study was to investigate the relationship between serum hepatocyte growth factor level with inflammation markers and the clinical features of patients with pancreatobiliary cancer. Methods: A total of 62 patients with pancreatobiliary cancer were included in this study. Serum hepatocyte growth factor concentrations were evaluated utilizing the enzyme-linked immunosorbent assay method. Results: The median serum hepatocyte growth factor level was 329.1 ng/mL (1.4-1051.1). The patients were categorized into 2 groups as those below the median hepatocyte growth factor level (low hepatocyte growth factor) and those above the median hepatocyte growth factor level (high hepatocyte growth factor). While 40.9% of the patients without metastasis were observed to be in the high hepatocyte growth factor group, 72.2% of the metastatic patients were observed to be in the high hepatocyte growth factor group (P = .025). The median levels of monocyte, monocyte-to-lymphocyte ratio, C-reactive protein, and C-reactive protein-to-albumin ratio were found to be significantly higher in the high hepatocyte growth factor group as compared to the low hepatocyte growth factor group (P < .050). Conclusion: The significant relationship between serum hepatocyte growth factor level and systemic inflammation markers in patients with pancreatobiliary cancer is shown for the first time in our study. This study, which showed a significant relationship between the presence of metastasis and serum hepatocyte growth factor level, suggests that serum hepatocyte growth factor level may be a prognostic biomarker in patients who are diagnosed with pancreatobiliary cancer. Cite this article as: Ünek İT, Öztop İ, Başbınar Y, et al. Association of serum hepatocyte growth factor level with systemic inflammatory biomarkers in patients with pancreatobiliary cancer. Turk J Gastroenterol. 2023;34(5):568-575.